Investments in Higher Education and the Economic Performance of OECD Member Countries - Amnon Frenkel; Eran Leck (European Regional Science Association (ERSA), 2006)
Universities and academic research institutions play an important role in contributing to the economic growth of countries, mainly through the diffusion of scientific knowledge, new methods, and technologies. This study investigates the relationship between investments in higher education and the economic performance of developed countries. Cross-sectional data, relating to higher education, workforce composition, and macro-economic indicators, were analyzed. The empirical analysis was based on data gathered from international datasets: World Development Indicators (WDI) of the World Bank, OECD Statistics Portal, and UNSECO for the 30 OECD member states. The main research hypothesis was that a positive and significant linkage exists between investment in higher education and economic growth. The examination was carried out by employing two models. The first model (a two-stage model) assumed that an indirect link existed between higher education and economic growth. The instrumental indicator used in the analysis was the country's labor force composition (specifically, the percentage of employees in scientific and engineering fields). The second model employed a multivariate regression model to directly test the relationship between higher education and growth indicators. The research findings show that higher education inputs translate into human capital outputs (a trained workforce in the computing, science, and engineering fields), and these transform back into the inputs that explain the economic performance of OECD countries. Smaller European countries, such as Finland, the Netherlands, and Denmark, are more efficient in translating their educational investments into a high-quality labor force. The two main activities of universities - teaching and research - were found to be connected to enhancing the per capita GDP of OECD countries. The research findings also support evidence from other studies that show decreasing returns to scale in education. The elasticity of per capita GDP with respect to R&D expenditure per student and the expenditure on teaching in research universities were found to be fairly large, with a constant elasticity of 0.78% and point elasticities (when expenditure on teaching is held constant) ranging from 0.04% (Turkey) to 0.84% (Sweden). Point elasticities for the majority of OECD countries were found to be at the 0.2%-0.5% level.
Keywords: 330